2020
DOI: 10.1039/d0nr02543g
|View full text |Cite
|
Sign up to set email alerts
|

A continuous stimuli-responsive system for NIR-II fluorescence/photoacoustic imaging guided photothermal/gas synergistic therapy

Abstract: A step-by-step stimuli-response nanosystem that could be specifically activated by a “multistage rocket-like” process to improve its NIR-II/PA signals for imaging-guided photothermal/gas synergistic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…[16] Despite significant progress in anticancer activity, unfortunately, most of the reported nanotheranostics still suffer from pronounced limitations, especially insufficient tumor accumulation and nonspecific biodistribution. [17,18] The tumor cells are generally known to distinguish different from normal cells. [19] Due to the disordered metabolic pathways and specific physiological mechanism of tumor, the tumor microenvironments (TME) perform unique characteristics such as acidic matrix, overproduced hydrogen peroxide (H 2 O 2 ), and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Despite significant progress in anticancer activity, unfortunately, most of the reported nanotheranostics still suffer from pronounced limitations, especially insufficient tumor accumulation and nonspecific biodistribution. [17,18] The tumor cells are generally known to distinguish different from normal cells. [19] Due to the disordered metabolic pathways and specific physiological mechanism of tumor, the tumor microenvironments (TME) perform unique characteristics such as acidic matrix, overproduced hydrogen peroxide (H 2 O 2 ), and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ag 2 S QDs have been integrated into theranostic nanoplatforms combining fluorescence and PA imaging with PTT, [ 81 ] PTT plus computed tomography (CT), [ 52,53 ] and PTT plus gas therapy (GT). [ 82 ] For example, Tang et al. synthesized Ag 2 S QDs in human serum albumin (HSA) nanocages with precise size control for PTT with fluorescence and PA imaging guidance ( Figure a).…”
Section: Bioapplications Of Nir Ag2s Qdsmentioning
confidence: 99%
“…designed and constructed an activatable theranostic nanoplatform (Ag 2 S@M/D‐P‐RGD) by biomineralizing Bi 2 S 3 , Ag 2 S, and diallyl trisulfide (DATS) in BSA, and functionalizing the nanoparticles with 3‐azidopropylamine (N 3 (−) ). [ 82 ] As shown in Figure a, the encapsulated DATS released H 2 S gas when triggered by excess GSH in the tumor microenvironment. In addition to providing gas therapy, the released H 2 S enhanced tumor‐specific aggregation by reducing N 3 (−) to NH 2 (+) .…”
Section: Bioapplications Of Nir Ag2s Qdsmentioning
confidence: 99%
“…Metal sulfides, such as copper sulfide (CuS), tungsten sulfide (WS 2 ), and molybdenum sulfide (MoS 2 ), have been widely used for PAI and photothermal therapy (PTT) as novel optical molecular imaging reagents [35][36][37][38][39]. Taking Cu 2-x S as an example, recent research revealed that the LSPR effect could be regulated by altering the composition ratio of Cu/S to realize the application of Cu 2-x S in NIR-II PAI.…”
Section: Metal Chalcogenides-based Nanomaterialsmentioning
confidence: 99%